Posterior shoulder dislocation while lifting weights: a missed diagnosis. (20th February 2014) - Cuffolo, Giulio; Coomber, Ross; Burtt, Simon; Gray, Jim
Summary: We present a case of a 24-year-old man who suffered acute shoulder pain and subsequent inability to move his arm while lifting weights in the bench-press position. He attended A&E where he was examined and X-rays were performed. He was diagnosed with presumed pectoralis major tendon rupture and was discharged to fracture clinic the following day with analgesia. On review in clinic he was found to have a posterior shoulder dislocation and was taken to theatre for relocation under anaesthesia. This case report examines the mechanism, investigations and management of posterior shoulder dislocation.